Spoken Words Specify to the Style of Speech in Fiction, the Factors of Their Formation on Speech and Difficulties in Translation - Rakhimova Irodakhon Bakhodirovna (Periodica Journal, 2022)
In recent decades, the emphasis has been on the study of language along with its owner, its national mentality and national culture. But, stagnant rules of morality, values, features of the national mentality of the people, reflected in the stable units of language formed over the centuries. Linguistic and cultural study of spoken words in the Uzbek language is great importance in highlighting the essence of the mentality of the Uzbek nation, the peculiarities of the national consciousness, the system of values. The language reflects the customs, way of the life, economic condition of the people, in short, the boredom of the people. Knowing the language of a particular people means understanding its entire existence. Spoken words do not appear spontaneously. There are a number of factors that shape them. First of all, it is one of the main means of the main means of national characteristics, nationality, customs of the nation.
Keywords: Spoken Words; Lexical Units; Words And Phrases; Lexico-Semantic Analysis